The Dynamics of Some Market Indicators - D. Y. Ivanov; P. A. Dmitriev (Высшее образование в России, 2020)
The purpose of this article is to study the dynamics of some market indicators for “paid” publications. The authors analyze scientific articles, data from Google Trends on requests characterizing the dynamics of the market, data from student journals published by top sites offering paid publishing services. The main research method is content analysis of data using automated tools of the MS Office suite and the VBA environment. The authors note that supply and demand in the “paid” publications market are formed under the influence of state policy in the field of university ranking, stimulating scientists and students. According to the data regarding inquiries over 5 years, there has been a positive trend. The popularity of the «RSI publication» request has grown by 300% since January 1, 2017. The authors also show an increase in the selected student journals. The authors note the steady growth of the market for “paid” publications and point out that a number of measures applied do not work or may even adversely affect the development of Russian science. The authors discuss possible measures to remedy the situation, agreeing with the position of some scientists and objecting to others.